2017
DOI: 10.1021/acs.est.7b03126
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Coupled Anaerobic Oxidation of Methane Performed by a Mixed Bacterial-Archaeal Community Based on Poorly Reactive Minerals

Abstract: Anaerobic oxidation of methane (AOM) was shown to reduce methane emissions by over 50% in freshwater systems, its main natural contributor to the atmosphere. In these environments iron oxides can become main agents for AOM, but the underlying mechanism for this process has remained enigmatic. By conducting anoxic slurry incubations with lake sediments amended with C-labeled methane and naturally abundant iron oxides the process was evidenced by significantC-enrichment of the dissolved inorganic carbon pool and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
120
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 80 publications
15
120
2
Order By: Relevance
“…lakes with a temporary or permanently anoxic hypolimnion) of the temperate zone strongly suggests that aerobic MOBs dominate CH 4 oxidation in both oxic and anoxic water layers (Biderre-Petit et al 2011, Blees et al 2014, Oswald et al 2015, 2016a. Aerobic MOBs were also recently seen to dominate anaerobic CH 4 oxidation in sub-arctic and temperate lake sediments (Bar-Or et al 2017, Martinez-Cruz et al 2017. Under oxygen limitation, MOBs may efficiently use the limited O 2 to activate CH 4 and are suggested to further support their metabolism by fermentation (Kaly uzhnaya et al 2013) or by anaerobic respiration using alternative EAs, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…lakes with a temporary or permanently anoxic hypolimnion) of the temperate zone strongly suggests that aerobic MOBs dominate CH 4 oxidation in both oxic and anoxic water layers (Biderre-Petit et al 2011, Blees et al 2014, Oswald et al 2015, 2016a. Aerobic MOBs were also recently seen to dominate anaerobic CH 4 oxidation in sub-arctic and temperate lake sediments (Bar-Or et al 2017, Martinez-Cruz et al 2017. Under oxygen limitation, MOBs may efficiently use the limited O 2 to activate CH 4 and are suggested to further support their metabolism by fermentation (Kaly uzhnaya et al 2013) or by anaerobic respiration using alternative EAs, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been suggested that in situ oxygen production by photosynthetic algae or episodic oxygen introduction, events from the surface waters (Blees et al 2014) could fuel MOBs in the anoxic waters. However, indirect evidence from lake sediments suggests that MOBs could also drive AOM independently of any external O 2 source (Bar-Or et al 2017, Martinez-Cruz et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently anaerobic methanotrophic archaea (ANME) were visualized in sediments and shown to form multicelled aggregations with deltaproteobacteria bacteria, spanning from micron‐scale aggregates to mats covering meter‐scale reef‐like structures (Boetius et al, ; Orphan et al, ; Orphan et al, ; Michaelis et al, ). Since then, our understanding of the diversity of ANME archaea and bacteria involved in this process has expanded along with a growing list of terminal electron acceptors coupled to methane oxidation, including nitrate (Haroon et al, ; Raghoebarsing et al, ); iron and manganese (Beal et al, ; Ettwig et al, ; Barr‐Or et al, ); and humic acid analogs (Scheller et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, SO 4 is present, but AOM appears partially or entirely decoupled from sulfate reduction (Beal, House, & Orphan, 2009;Gupta et al, 2013;Segarra, Comerford, Slaughter, & Joye, 2013;Segarra et al, 2015;Sivan, Antler, Turchyn, Marlow, & Orphan, 2014). Despite the growing number of reports on Fe-dependent CH 4 oxidation (Bar-Or et al, 2017;Cai et al, 2018;Egger et al, 2015;Ettwig et al, 2016;Fu et al, 2016;Gao et al, 2017;Nordi et al, 2013;Roland et al, 2018;Scheller, Yu, Chadwick, Mcglynn, & Orphan, 2016), the pathway remains unsubstantiated through pure culture experiments and its broader ecological importance is as yet unknown. Lake Matano, Sulawesi Island, Indonesia, is situated near the equator and hosts the largest, deepest, and oldest known ferruginous basin on Earth (Crowe, Jones, et al, 2008;.…”
mentioning
confidence: 99%